Ergonomic Analysis of Working without Fatigue and Increasing Work Productivity - Santoso, Gempur; Prihono (Tibuana, 2022)
Currently, there is still hard work going on, but the income is not adequate. Therefore, it is necessary to show scientifically that working does not need to be tired, but with an ergonomic system, productivity increases. This paper is made from various books or literature scientifically and analyzed and discussed descriptively. Conclusion: first, at work, an ergonomic tool must be made, so that at work it is enough to use body energy of 5.0 kcal/hour to 5.2 kcal/hour, so that work is in the heavy category, because using ergonomic tools and systems becomes work in the light and even relaxed category. Second, the application of ergonomics in various fields of work can improve work optimally, and productivity can increase between 10% to 21.28%. Suggestion: It is better to work without wasting the body's energy which makes you tired easily, by providing equipment technology and ergonomic systems.